TRACKING THE EXTENSION OF THE SEMANGGOL FORMATION USING REMOTE SENSING AND GIS TECHNIQUES - Tan Jianming , Nicholas (Universiti Teknologi PETRONAS, 2016)
This study is aimed to track the extension of the Semanggol Formation exposed around the northern states of Malaysia using remote sensing and GIS techniques. The Semanggol Formation has been recorded as segments of three parts separated by the Mahang Formation and igneous rocks although the exact boundary is not known and still remains a mystery due to the lack of stratigraphic contact and good research. This study plans uses remote sensing technology as a supplementary technique to previous works, which has never been applied, to get a better understanding of this. Landsat 8 data is used for remote sensing analysis and it is found that the boundaries are similar to what has been defined by past researches. Due to the nature of Malaysia’s climate which causes lush vegetation that covers the earth’s surface and the developed areas, the usage of remote sensing analysis to detect lithology has been heavily limited.